2016
DOI: 10.1037/rel0000045
|View full text |Cite
|
Sign up to set email alerts
|

Christian religious badges instill trust in Christian and non-Christian perceivers.

Abstract: We conducted 4 experiments to examine how people incorporate visual information about strangers' religious identities-religious badges-into their decisions about how much to trust them. Experiment 1 revealed that Christian and non-Christian participants were more trusting (as measured by self-report) of targets who wore a religious badge associated with Christianity (Ash Wednesday ashes) than toward targets who did not wear such a badge. Experiment 2 replicated Experiment 1 and also revealed that the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 51 publications
5
41
0
Order By: Relevance
“…The results reported here extend experimental work showing that religious individuals are often perceived as more trustworthy (Hall et al, 2015;McCullough et al, 2015;Purzycki and Arakchaa, 2013;Ru✏e and Sosis, 2010;Tan and Vogel, 2008;Widman et al, 2009). Here, I have drawn on quantitative ethnographic evidence to show that reputational evaluations of one's peers are shaped, in part, by the religious practice they undertake.…”
Section: Discussionsupporting
confidence: 77%
“…The results reported here extend experimental work showing that religious individuals are often perceived as more trustworthy (Hall et al, 2015;McCullough et al, 2015;Purzycki and Arakchaa, 2013;Ru✏e and Sosis, 2010;Tan and Vogel, 2008;Widman et al, 2009). Here, I have drawn on quantitative ethnographic evidence to show that reputational evaluations of one's peers are shaped, in part, by the religious practice they undertake.…”
Section: Discussionsupporting
confidence: 77%
“…This finding is interesting given different affective responses among religious groups (Gallup, ; Pew Research Center, ) as well as prior research showing that religious cue usage in marketing communications generally increases product evaluations (Dotson & Hyatt, ; Minton, ; Taylor et al, ). These findings are particularly interesting in that they also contradict a large body of prior research showing a positive halo effect of religion on evaluations of people (c.f., Bailey & Vietor, ; Bailey & Young, ; Isaac, Bailey, & Isaac, ) as well as greater trust of religious people (c.f., Gervais, Shariff, & Norenzayan, ; McCullough, Swartwout, Shaver, Carter, & Sosis, ; Moon, Krems, & Cohen, ). Put simply, results from the studies herein suggest that religious cues do not have the same effect for products as they do for people.…”
Section: Discussionmentioning
confidence: 99%
“…We sought to measure trait trustworthiness with McCullough, Swartwout, Shaver, Carter, and Sosis's () modified version of Evans and Revelle's () propensity to trust scale, which retained the seven items that McCullough et al found to have the highest item‐total score correlations. Responses were measured on a 5‐point rating scale (1 = strongly disagree, 2 = disagree, 3 = neither agree nor disagree, 4 = agree, 5 = strongly agree).…”
Section: Methodsmentioning
confidence: 99%